Hyperoxic preconditioning in partial liver ischemia - Margarido,Maria Rita (2014)
PURPOSE: To evaluate the effect of the hyperbaric oxygen (HBO) treatment as a pre-conditioning for I/R effects in the liver ischemia. METHODS: Fifty-seven male Wistar rats (260-300g) were submitted to the following procedures: SHAM; I/R, rats submitted to I/R, consisting of partial ischemia of 70% of the liver for 90 minutes followed by 15 minutes of reperfusion; HBO I/R 1 ATA, 30 minutes of HBO treatment at the pressure of 1 absolute atmosphere (ATA) during the ischemia time. HBO I/R 2 ATA, 30 minutes of HBO (2 ATA) during the ischemia time. Pre HBO I/R 30', rats submitted to 30 minutes of HBO (2 ATA) immediately before the I/R time. Pre HBO I/R 90', rats submitted to 90 minutes of HBO (2 ATA) immediately before the I/R time. RESULTS: There was a significant worsening of all the parameters of mitochondrial energy production (state 3, 4, RCR and Swelling) in the I/R group, when compared to the Sham group (I/R <Sham, p<0.05). There was also a significant worsening in state 4, RCR and mitochondrial edema in the Pre HBO I/R 90' group compared to the I/R group. Hepatic enzyme concentrations were significantly higher in the I/R group. CONCLUSION: The use of hyperbaric oxygen before and during I/R did not improve the production of hepatocellular energy reduced by I/R, nor did it prevent the installation of mitochondrial edema induced by Iischemia/reperfusion.